Is emotional maltreatment in childhood a predictor of risk-taking behaviours in adults? - Cross, Kathryn (2019)
The aim of this study was to investigate the relationship between emotional maltreatment (neglect and abuse) and risk-taking (risk-taking and risk assessment) behaviours. The study analysed subsequent links between emotional maltreatment, risk-taking behaviours and personality. The Childhood Trauma Questionnaire (Short form) measured participants childhood abuse, the HEXACO-60 was used to measure participants personality, and the RT-18 risk-taking questionnaire was used to measure participants risk taking and risk assessment. The questionnaires were administered online, with the target demographic being any gender, over the age of 18. Results showed that women experienced or recalled more emotional maltreatment than men, but inconsistent with previous research was that there were no gender differences in risk taking behaviours. There was a small positive correlation between emotional neglect and risk taking. Both positive and negative correlations between emotional maltreatment and personality were found, particularly a negative correlation between extraversion and emotional maltreatment. Consistent with previous research were associations between personality and risk-taking behaviours, especially risk assessment and conscientiousness. Overall, results from this study add to current literature on personality, emotional maltreatment and risk-taking behaviours, and can be developed for future research.